A management strategy for burns surgery in hemophilia complicated by inhibitors: A case report - L. Kearney; M. Abrahams; N. O'Connell; O.P. Shelley (Elsevier, 2023)
Few reports exist in the literature dealing with the management of acute burns in the hemophilic patient [1-4]. Burns treatment in this population group is an obvious challenge, due to the recognized major blood loss that can result from both the burns excision and harvesting split thickness skin grafts. Recent proposed strategies have suggested structured factor replacement during multiple radical short operations [3]. We describe a particularly challenging case, a person with mild Factor VIII deficiency (Hemophilia A) with a history of a high responding inhibitor and cross-reactivity with standard Factor VIII products. We propose a management strategy to optimise care and reduce bleeding related complications in these patients.